1996
DOI: 10.1007/bf00328732
|View full text |Cite
|
Sign up to set email alerts
|

A native nitrogen-fixing shrub facilitates weed invasion

Abstract: Invasions by exotic weedy plants frequently occur in highly disturbed or otherwise anthropogenically altered habitats. Here we present evidence that, within California coastal prairie, invasion also can be facilitated by a native nitrogen-fixing shrub, bush lupine (Lupinus arboreus). Bush lupines fix nitrogen and grow rapidly, fertilizing the sandy soil with nitrogen-rich litter. The dense lupine canopy blocks light, restricting vegetative growth under bushes. Heavy insect herbivory kills lupines, opening expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
241
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 278 publications
(255 citation statements)
references
References 36 publications
8
241
4
Order By: Relevance
“…It appears that native functional groups have a nurse effect on bitou seedlings and moderate environmental conditions. Nurse effects of native species on invader germinants have been documented by previous studies which have reported facilitative effects through reducing light and temperature extremes (Lenz & Facelli 2003) and increasing water and nutrient availability (Maron & Connors 1996;Cavieres et al 2005) under canopies of existing native species compared with uncolonised areas. In our study, bare ground cover was significantly higher in the unplanted than planted treatments.…”
Section: Planted Treatments Facilitate Bitou Germination But Suppressmentioning
confidence: 80%
“…It appears that native functional groups have a nurse effect on bitou seedlings and moderate environmental conditions. Nurse effects of native species on invader germinants have been documented by previous studies which have reported facilitative effects through reducing light and temperature extremes (Lenz & Facelli 2003) and increasing water and nutrient availability (Maron & Connors 1996;Cavieres et al 2005) under canopies of existing native species compared with uncolonised areas. In our study, bare ground cover was significantly higher in the unplanted than planted treatments.…”
Section: Planted Treatments Facilitate Bitou Germination But Suppressmentioning
confidence: 80%
“…Only after the death of nitrogen fixers do other invaders tend to increase (e.g. Maron & Connors 1996;Adler et al 1998). Thus, while it is clear that invaders can alter nitrogen cycling, it is less clear that this impact per se changes community structure.…”
Section: Mechanisms Of Impact On Ecosystem Processesmentioning
confidence: 99%
“…Native species often are better adapted to lower N levels present in the unaltered ecosystem (Arendt 1997;Hobbie 1992;McLendon and Redente 1992). In contrast, many invasive exotic species are well adapted to exploiting high N sites and have high dispersal rates that allow rapid colonization (Cousens and Mortimer 1995;Maron and Connors 1996;Rejmanek and Richardson 1996). Once at a N-rich site, exotic species can exploit N more quickly than later successional natives by increasing growth rates in response to higher nutrient availability (Carson and Barrett 1988;Fogarty and Facelli 1999).…”
Section: Introductionmentioning
confidence: 99%